OP0292 Genetic variation associated with cardiovascular risk in autoimmune diseases. (15th June 2017) - Aterido, A; Cañete, JD; Fernández-Nebro, A; Ferrándiz, C; Tornero, J; Pérez-Gisbert, J; Domènech, E; Fernández-Guitiérrez, B; Gomollόn, F; García-Planella, E; Fernández, E; Sanmartí, R; et al.
Abstract : Background: Autoimmune diseases are highly disabling chronic disorders characterized by the activation of multiple immune and inflammatory pathways against self-components. Clinical studies have demonstrated that autoimmune diseases have a higher prevalence of cardiovascular events compared to the general population. Understanding the genetic and biological mechanisms underlying cardiovascular disease (CVD) risk in autoimmunity could therefore be fundamental to develop more efficient preventive and therapeutic strategies. Objectives: The objective of this study was to characterize the genetic basis of CVD risk in autoimmune diseases. Methods: A total of 6, 485 patients from the six autoimmune diseases RA, PA, SLE, PS, CD and UC were recruited by the Spanish biomedical consortium IMID Consortium. All patients were Caucasian European from the Spain. CVD patients were defined as having ≥1 out of the 3 most frequent cardiovascular phenotypes: (i) ischemic heart disease (ii) cerebrovascular accident and (iii) peripheral arterial disease. In order to characterize the genetic basis of CVD risk in autoimmune diseases, we used genome-wide genotyping data from all autoimmune disease patients included in the study. First, we tested the association of established CVD risk variants within each autoimmune disease. Second, we analyzed the association of autoimmune disease risk variants with an increase in CVD risk. Finally, we used the cross-phenotype meta-analysis approach (CPMA) to perform a genome-wide meta-analysis and identify global genetic patterns associated with CVD risk in autoimmune diseases. Results: A total of 17 loci previously associated with CVD risk in the general population were significantly associated with CVD risk in the autoimmune patient cohorts ( P <0.05). From these, 4 loci were found to have significantly different genetic effects across autoimmune diseases ( P <0.05). We also found that 6 risk loci for autoimmune diseases were associated with an increase in CVD risk, like the RA risk gene CFLAR-CASP8 . The CPMA identified a total of 10 genetic patterns significantly associated with CVD risk across all autoimmune diseases. Two of these patterns showed a highly significant association with CVD risk in RA, PsA and SLE. The functional analysis of these two genetic patterns revealed a significant enrichment in key pathways related to the etiology of rheumatic diseases like TNFα ( FDR <0.05) and IFNγ (FDR <0.05) cytokine pathways. Conclusions: The results of the present study represent an important step towards the characterization of the genetic basis of CVD in autoimmune diseases. These findings contribute to explain the higher prevalence of cardiovascular events observed in patients with autoimmune diseases compared to the general population. Disclosure of Interest: None declared